2019
DOI: 10.1051/kmae/2019033
|View full text |Cite
|
Sign up to set email alerts
|

New records of the invasive red swamp crayfishProcambarus clarkii(Girard, 1852) (Decapoda: Cambaridae) from Poland

Abstract: This contribution presents new observations of the red swamp crayfish, Procambarus clarkii in Poland. The species was detected in Żerań Canal and Krasiński Garden in Warsaw (central Poland) where 5 and 2 individuals were collected respectively as well as in Dąbie Pond in Krakow (southern Poland) with total of 4 crayfish observed. These new sites are located approximately 500 km eastward (Warsaw) and 240-260 km northward (Krakow) from the nearest European sites where this species has been previously recognised … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 42 publications
(49 reference statements)
0
7
0
Order By: Relevance
“…Furthermore, crayfish are increasingly being viewed as suitable animals for aquaculture and also for aquarium breeding. Quite recently a new invasive species, the red swamp crayfish Procambarus clarki (Girard, 1852), has been recorded at several sites in the upper and middle segments of the Vistula River basin, which are the potential sites for specie's spread to the lower catchment (Maciaszek et al, 2019). Globally, this animal is one of the worst invasive crayfish species (Gherardi, 2007;Chucholl, 2011;Capinha et al, 2013;Twardochleb et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, crayfish are increasingly being viewed as suitable animals for aquaculture and also for aquarium breeding. Quite recently a new invasive species, the red swamp crayfish Procambarus clarki (Girard, 1852), has been recorded at several sites in the upper and middle segments of the Vistula River basin, which are the potential sites for specie's spread to the lower catchment (Maciaszek et al, 2019). Globally, this animal is one of the worst invasive crayfish species (Gherardi, 2007;Chucholl, 2011;Capinha et al, 2013;Twardochleb et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…These vectors have led to established populations across Europe, Africa, Asia, and the Americas. The red swamp crayfish is considered a warm water species (Zhang et al 2020), but has been shown to survive for months at low temperatures (Veselý et al 2015;Haubrock et al 2019), and has established populations in colder climates than its native range (e.g., Poland; Maciaszek et al 2019). Red swamp crayfish is present in the ecoregion in US waters but has yet to be found in the Canadian portion of the Great Lakes (Peters et al 2014;Smith 2018;O'Shaughnessey et al 2021), although nearshore warm areas of the Canadian Great Lakes do provide suitable habitat (Egly et al 2019).…”
Section: Laurentian Great Lakesmentioning
confidence: 99%
“…In Polish waters, it was first found in the Samica River in 2014 (Fig. 1C; GDOS 2018), and in a small pond by the Vistula River near Kraków and Warsaw in 2018, where it most likely escaped from breeding or was deliberately released by aquarists (Maciaszek et al 2019).…”
Section: Introductionmentioning
confidence: 99%